Upaya Peningkatan Nilai Ekonomi Produk UMKM Melalui Pemanfaatan Marketplace sebagai Platform Pemasaran Digital: (Studi Kasus pada Sinar Timur, Desa Tanjung Luar, Keruak, Lombok Timur) - Yuniar Affandy; Salmi Yuniar Bahri; Masbullah Masbullah; Asria Romdiana; Mutiara Hafsah (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
One form of enterprise that represents the potential of villages and receives government support is Micro, Small, and Medium Enterprises (MSMEs). However, limitations in marketing have led to the underrepresentation of local products. This highlights the importance of community service programs. The aim of this program is to enhance the marketing of UMKM products through the utilization of the Shopee marketplace and WhatsApp Business social media. The community service methods used include socialization, training, and direct assistance to UMKM actors in the target area. Shopee is utilized as an online marketplace, while WhatsApp Business serves as a medium for product advertising. This activity aims to provide understanding of the importance of digital marketing, as well as practical skills in creating and managing accounts on Shopee and WhatsApp Business. The results of this program indicate an increase in participants' understanding and ability to use both platforms. The conclusion of this research states that the effective utilization of Shopee and WhatsApp Business can assist UMKM actors in enhancing their marketing and sales, which in turn can drive local economic growth.